Consequence of cenosphere loading on hygrothermal, thermal, and mechanical properties of epoxy syntactic foams. (May 2019) - Kaur, Mandip; Jayakumari, LS
Epoxy syntactic foams with different compositions of cenosphere were fabricated and characterised. The effect of loading cenosphere in epoxy syntactic foams was analysed. Good thermal stability of cenosphere–epoxy syntactic foams was established from the thermogravimetric analysis results. The completion of cure reaction at ambient temperature conditions was ascertained from differential scanning calorimetry results. Dynamic mechanical analysis revealed 114°C as the glass transition temperatures ( Tg ) for neat epoxy sample, which increased to 132°C with 50% loading of cenosphere. Cenosphere-filled epoxy syntactic foams had low density and low water absorption values when compared to the neat epoxy sample. Homogeneous distribution of the cenosphere particles was confirmed using scanning electron microscopy. The compression studies confirmed brittle failure of the syntactic foams. This was also supported by the scanning electron microscopic images. The incorporation of hollow cenosphere particles led to a decrease in the flexural strength. Syntactic foams with 30% loading of cenosphere exhibited best specific modulus and specific strength. The specific strength increased by 24% for T30 sample and specific modulus increased by 36% for T30 samples when compared to the neat epoxy sample. As the need for strong but lightweight thermally stable products is continually increasing, there is a great possibility for the utilisation of these cenosphere–epoxy syntactic foams as lightweight core for sandwich composites.